2005
DOI: 10.1074/jbc.m508658200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Glucocorticoid-induced Leucine Zipper Protein in Epithelial Sodium Channel-mediated Sodium Transport

Abstract: The steroid hormone aldosterone stimulates sodium (Na ؉ ) transport in tight epithelia by altering the expression of target genes that regulate the activity and trafficking of the epithelial sodium channel (ENaC Hormone-regulated sodium (Na ϩ ) transport in tight epithelia is essential for the control of circulatory volume, blood pressure, and extracellular fluid composition in vertebrates. The epithelial Na ϩ channel, ENaC, 5 constitutes the rate-limiting step for Na ϩ transport, and its activity, trafficking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 55 publications
10
168
1
Order By: Relevance
“…RNA interference experiments also supported a role for GILZ in the inhibition of CXCL8 expression in endothelial cells (Eddleston et al, 2007). On the other hand, GILZ stimulated rather than suppressed the expression and activity of the epithelial sodium channel α (ENaCα) (Bhalla et al, 2006;Soundararajan et al, 2005), possibly via inhibition of the ERK pathway (Ayroldi et al, 2002;Soundararajan et al, 2005). ENaCα expression is thought to contribute to GC-induced hypertension (Fuller et al, 2000;Itani et al, 2002;Sayegh et al, 1999;Stokes and Sigmund, 1998).…”
Section: A Clarkmentioning
confidence: 89%
See 1 more Smart Citation
“…RNA interference experiments also supported a role for GILZ in the inhibition of CXCL8 expression in endothelial cells (Eddleston et al, 2007). On the other hand, GILZ stimulated rather than suppressed the expression and activity of the epithelial sodium channel α (ENaCα) (Bhalla et al, 2006;Soundararajan et al, 2005), possibly via inhibition of the ERK pathway (Ayroldi et al, 2002;Soundararajan et al, 2005). ENaCα expression is thought to contribute to GC-induced hypertension (Fuller et al, 2000;Itani et al, 2002;Sayegh et al, 1999;Stokes and Sigmund, 1998).…”
Section: A Clarkmentioning
confidence: 89%
“…GCs upregulate glucocorticoid inducible leucine zipper (GILZ) expression in T cells (Asselin-Labat et al, 2004;D'Adamio et al, 1997;Mittelstadt and Ashwell, 2001;Riccardi et al, 2001), mast cells , eosinophils (Arthaningtyas et al, 2005), epithelial (Bhalla et al, 2006;Chivers et al, 2006;Eddleston et al, 2007;Soundararajan et al, 2005;Wang et al, 2004), and myeloid cells (Berrebi et al, 2003;Cohen et al, 2006;Ehrchen et al, 2007). Relatively high basal GILZ expression has also been recorded in brain, lung and skeletal muscle .…”
Section: Glucocorticoid Inducible Leucine Zippermentioning
confidence: 99%
“…Recent evidence supports the idea that the Raf-interacting protein glucocorticoid-induced leucine zipper protein 1 (GILZ1) increases plasma membrane ENaC in part by antagonizing the inhibitory effect of the Raf-MEK-ERK module (10,11).…”
mentioning
confidence: 82%
“…The use of EGF to activate ERK1/2 in these cells through stimulation of endogenous EGF receptor is well described (19,20), and we have shown that activated ERK1/2 inhibits surface ENaC and GILZ1 reverses this process (10). Hence HEK 293T cells offered a useful system for examining regulatory factors that potentially govern ENaC surface expression.…”
mentioning
confidence: 99%
“…Because of the variety of protein interactions and its abundance in several cell types, GILZ has, in fact, a crucial role in controlling protein trafficking and signaling. Most recently, novel functions have been defined, including regulation of T helper cell differentiation 72,73 and DC function, 74,75 increase of epithelial Na þ channel-mediated Na þ transport in the kidney, 76,77 and control of malignant transformation through inhibition of Ras-driven tumorigenesis. 71,78,79 Young adult GILZ-overexpressing transgenic mice exhibit dramatically reduced numbers of CD4 þ CD8 þ thymocytes and increased ex vivo thymocyte apoptosis.…”
Section: Role Of Caspase-8 In Gc-induced Apoptosis In Thymocytesmentioning
confidence: 99%